The Effect of Tenure Audit, Kap and Audit Committee Reputation on Audit Quality - Zullivien Imamta; Henryanto Wijaya (Green Publisher Indonesia, 2025)
The purpose of this study is to find out whether there is an influence of audit tenure variables, the reputation of KAP and the audit committee on audit quality (a study on transportation and logistics companies in 2021-2023 listed on the Indonesia Stock Exchange) This type of research is quantitative, using secondary data and the total population of 95 transportation and logistics companies during 2021-2023, The sampling technique in this study is purposive sampling using the criteria of transportation and logistics companies that are registered continuously during 2021-2023 and companies that have reported audit finances during 2021-2023, the number of samples in this study is 75 companies. The analysis data used by SPSS software version 26. The results in this study stated that the audit tenure variable had a positive and significant effect on audit quality, the KAP reputation variable had a positive and significant effect on audit quality, the audit committee had no effect on audit quality and the audit tenure variable, the reputation of KAP and the audit committee had a simultaneous effect on audit quality. The benefits in this study can be used as information for future researchers in the development of research in the field of audit quality.